Isolation and characterization of a new potential source of bioactive peptides: White mulberry (Morus alba) fruits and its leaves - Fatma Tuba Kirac; Didem Sahingil; Ali Adnan Hayaloglu (Food Chemistry Advances, 2024)
In this study, white mulberry (WM; Morus alba L.) and its leaf (WML) were hydrolyzed using enzymes at different preheating temperatures (50, 60, 70, 80, and 90 °C) with distilled water at a ratio of 1:10 (w/v). Pepsin, trypsin, chymotrypsin, and alcalase were employed for enzymatic hydrolysis, aiming to investigate the impact of heat treatment and enzymatic hydrolysis on bioactive properties; in particular, angiotensin-converting enzyme-inhibitory (ACE-i) and antioxidant activities. The highest hydrolysis efficiency was observed when using pepsin. The smaller peptides with <3 kDa had better ACE-i and antioxidant activities in both WM and WML samples. Regarding antioxidant activity, the highest level was identified at a preheating temperature of 90 °C in the WM sample, and at preheating temperatures of 50 °C and without heating in the WML samples. In conclusion, heat treatment and enzymatic hydrolysis were found to be a positive impact on ACE-i and antioxidant activities under various conditions. Moreover, the proteins derived from WM and WML were rich in the sources of potential ACE-i and antioxidant peptides.